Legal Status of Persons Performing Work Through Internet Platforms – In Search of a Model of Protection - Naumowicz, Kamila (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The COVID-19 pandemic has highlighted numerous problems regarding the legal protection of persons performing work via online platforms, resulting, inter alia, from the formal qualiﬁcation of these workers as self-employed by the platforms. The lack of job stability, protection in terms of salary, social protection or even safe and healthy working conditions caused a wave of protests in many European countries and resulted in rich jurisprudence deﬁning the criteria of determining the legal status of persons performing work via online platforms. It also prompted the EU legislator to improve the working conditions of this group of workers, as evidenced by the draft of the EU directive on the improvement of working conditions through online platforms published in December 2021. The aim of this study is to present the legal dilemmas related to the determination of the legal status of persons providing work via online platforms with reference to the jurisprudence of selected European countries and the solutions proposed by the European Commission. A critical assessment of the proposed regulations leads to a reﬂection on the appropriate model of protection for these persons, beyond the dichotomous division into employee and non-employee status.